STRATEGI INDONESIA DALAM MENINGKATKAN EKSPOR KAYU LAPIS (PLYWOOD) KE INGGRIS - Sihotang, Esra Septia; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Indonesia is one of the top 5 plywood exporting countries to the UK, Indonesia's export volume has been stagnant since 2001-2008 at less than 2,000,000 USD. However, in 2009, the volume of Indonesian plywood exports to the UK decreased by 50% due to the birth of new competitors in the plywood trade to the UK. To maintain the position and volume of Indonesian plywood exports to the UK, efforts are being made. This research uses the theory of comparative advantage which highlights the trade advantage factor that can be achieved if a country that sells the same products as other countries, but is able to highlight competitive values, will be able to maintain and even increase its trade. The indicators in this theory are: 1.) production factors; 2.) currency; 3.) the condition of whether there is inflation or not; and 4.) trade barriers. Efforts made by Indonesia include increasing production of FLEGT - VPA (Forest Law Enforcement, Governance and Trade in Timber Products - Voluntary Partnership Agreement) and building cooperation in forest governance with the UK MFP (Multistakeholder Forestry Program) to increase UK confidence in the quality of exports plywood. Keywords: FLEGT-VPA, Indonesia Export, Plywood